Estudio de factibilidad para la instalación de una piscifactoría de tilapia roja oreochromis sp para el mercado de Pasaje El Oro - Guzmán Freire, Jorge Luis (2015)
The main objective of this proposal was to conduct a feasibility study for the installation of red tilapia farm in Pasaje, El Oro province, canton which began with a series of surveys to a group of inhabitants of the town of Passage , according to the results of the 2010 Census of Population and Housing INEC (www.ecuadorencifras.gob.ec), the Pasaje Canton has 23826 inhabitants in 72,806 households, this information could assess the market and estimate the subsequent consumption of Tilapia, for the number of surveys that were performed was taken as the base formula of INEC, within the market research, it was determined the size of the project. The proposal has two phases of pre-breeding (2 months) and a feeder at the end of the fattening period (4-5 months), survival is estimated at around 65%. (Marcillo, Landivar, 2007), and the fish will have a weight of between 400g to 600g, giving us a biomass pool 2059.2 Lbs (936 Kg.) And five pools, giving us a total biomass of 10296 Lbs . (4680 kg.), if all this work is done in a planned and operated with two (2) pools of pre-breeding and ten (10) feeders can be achieved in one year end 20 crops with a production of 41,184 Lbs. (18,720 kg.)